PENINGKATAN KEMAMPUAN MENGENAL LAMBANG BILANGAN DENGAN BERMAIN TUTUP BOTOL ANGKA PADA ANAK KELOMPOK A DI KELOMPOK BERMAIN BINA ANA PRASA III SAMARINDA TAHUN PEMBELAJARAN 2017/2018 - Wahyuni - Wahyuni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2018)
This study aimed to improve children’s capability in identifying Numeric Symbols by Playing the Bottle Caps Numbers in Group A at Play Groups BinaAna Prasa III Samarinda. This study was classroom action research which is done collaboratively between researcher and classroom teacher. This study conducted for two cycles. Each cycle was held for four meetings. Subject of this study were 15 children from Class A, there were 8 male and 7 female. This study conducted on July – August academic year 2017/2018. Data collection technique used observation and documentation that can be analyzed by looking for the percentage of children’s success. The results of this study indicate that the ability of children to recognize the symbol of the numbers 1-10 can be increased through the activities of playing the bottle cap numbers. The increase can be seen from the percentage improvement of children who got the criteria very well. The result before doing a treatment who reached the criteria develops very well at 7% or 1 child and develops as expected there were 3 children by 20%. In cycle I, the percentage of criteria develops very well increased to 40% or 6 children and percentage grew as expected 40% or 6 children. In cycle II, which got the criteria very well also grew, there was an increase to 87% or 13 children and developed as expected with the percentage of 13% that was 2 children. It could be concluded that by playing bottle caps numbers, it could improve children’s capability in identifying Numeric Symbols in Group A at Play Groups BinaAna Prasa III Samarinda.